2015
DOI: 10.4028/www.scientific.net/ddf.363.178
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Nitrogen Diffusion Enhancement Resulting from a NanoPeening® Treatment on a Pure Iron – Influence of the Grain Morphology

Abstract: It is well known that nanocrystalline materials have enhanced diffusion properties due to their high grain boundary density which act as fast diffusion channels compared to the lattice. In this paper, we aim at simulating the nitriding process of a pure iron nanostructured by NanoPeening® process. We use a simple diffusional approach taking into account the grain size and the grain morphology resulting from the NanoPeening® treatment. EBSD measurements are carried out to extract morphological parameters which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hence, the grain boundary diffusion occurs faster than the volume diffusion, and the penetration depth of atoms along the grain boundaries is much higher than intragranular diffusion. Also, increasing the concentration of solute atoms (such as nitrogen) at grain boundaries leads to their diffusion inside the grains [37]. About the diffusion of elements like nitrogen (capable of reacting chemically with the matrix atoms), it seems that in the early stage of nitriding, rapid diffusion of nitrogen atoms along grain boundaries causes an increase in the penetration depth.…”
Section: Sem Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the grain boundary diffusion occurs faster than the volume diffusion, and the penetration depth of atoms along the grain boundaries is much higher than intragranular diffusion. Also, increasing the concentration of solute atoms (such as nitrogen) at grain boundaries leads to their diffusion inside the grains [37]. About the diffusion of elements like nitrogen (capable of reacting chemically with the matrix atoms), it seems that in the early stage of nitriding, rapid diffusion of nitrogen atoms along grain boundaries causes an increase in the penetration depth.…”
Section: Sem Resultsmentioning
confidence: 99%
“…For unstable states, Fick's second law is used. Under this law, diffusion depth (case depth) is obtained as x≈√Dt, where x is case depth, D is diffusion coefficient, and t is treatment time [37]. In a study conducted by Lakhtin et al [39], the diffusion coefficient of nitrogen in ferrite has been reported as:…”
Section: Mechanism Of Decomposition Of Cementite Layersmentioning
confidence: 99%